ADDRESSING STRUCTURAL POVERTY IN KLUWUT VILLAGE FOR FISHERMEN FAMILIES - Pratysto, Tangguh; Sugiyanto, Fransiscus Xaverius; Yusuf, Maulana Ghani; Sanjoko, Deny Cahyadinanto; Fajri, Moh Najikhul (EZRA SCIENCE BULLETIN, 2025)
Brebes Regency is one of the areas with the highest poverty rates in Central Java. In Kluwut Village, although many residents have relatively high incomes as fishermen, poverty still occurs due to suboptimal household financial management and low awareness of children's nutrition and health. This community service program aims to identify the causes of poverty with a multidimensional approach based on Amartya Sen's theory, including fundamental inability, lack of freedom, and inequality. The methods include field observation, interviews with the community and village officials, and secondary data analysis. The results of the study show that the economic potential of Kluwut Village from the fisheries sector is quite large. However, unhealthy financial practices such as the habit of going into debt and high stunting rates are still a problem. Intervention programs such as providing healthy food and “Posyandu” are considered ineffective due to weak supervision and limited budget. Therefore, financial education is needed for fishing families, strengthening stunting interventions, and validating nutritional measurement tools. Continuous collaboration between academics, local governments, and the private sector is required in order to overcome structural poverty and improve the quality of life of the people in Brebes.